Phenomenology in nursing studies: New perspectives - Zahavi, D; Martiny, K (Elsevier, 2019)
Nursing studies have for decades drawn on the philosophical tradition of phenomenology when developing their own methodology and theoretical foundation. This use and application of phenomenology has, however, not been met with universal approval. One prominent and persistent opponent has been John Paley, who has sent a clear message to the nursing community: If you are looking for philosophical inspiration or methodological guidance, do not look to phenomenology. As we argue in the article, in formulating his criticism, Paley completely overlooks a rich tradition of applied phenomenology that dates back to the beginning of the 20th century and which has undergone a momentous revival during the last 20–25 years. That Paley seems oblivious to this tradition is one thing. What is more astonishing is that this also holds true for the vast majority of those scholars working within nursing science who happens to be interested in phenomenology. The aim of this article is, first, to present and consider Paley’s criticism in some detail and, then, to discuss some of the significant applications of phenomenology that have often been overlooked by qualitative researchers. As has been amply demonstrated over the years, phenomenology can not only make a difference in the handling, analysis, and interpretation of the available data, but also, in how the data are obtained in the first place, for instance, through special interview techniques. We will consider some central figures in classical phenomenological psychology and phenomenological psychiatry, and present some of the more recent developments in cognitive science. We will then discuss three concrete cases that demonstrate how phenomenology has been applied in clinical work with patients with schizophrenia, cerebral palsy, and hemispatial neglect. Our main message to qualitative researchers interested in phenomenology is the following. You should also start to consider and draw inspiration from the way in which phenomenology has been applied outside of the domain of qualitative research. There are quite successful applications of phenomenology to be found elsewhere, applications that can offer substantial theoretical and methodological support to qualitative researchers. Relevant resources include classical phenomenological psychology, classical and contemporary phenomenological psychiatry, and contemporary discussions of naturalized phenomenology.